Public Health In Socio-Cultural Determinants - Mujain Ahkyar; Bilal Zaula Rahman Rahman; Sultan Gustriadi (Journal of Health and Multidisciplinary Health Studies, 2026)
This article aims to examine how public health is influenced by socio-cultural determinants that develop within a community. Public health is not only determined by biological factors and health services alone, but is also greatly influenced by social, economic, educational, environmental, and cultural values held by individuals and community groups. These socio-cultural determinants shape mindsets, behaviors, and lifestyle habits, which ultimately have a direct impact on public health, both in terms of disease prevention and health care. In this context, understanding socio-cultural factors is crucial in efforts to improve the effectiveness of more holistic and sustainable public health programs. The research method used is library research with a qualitative descriptive approach. According to Zed (2021), a library study is a data collection method conducted through the review of various written sources such as books, scientific journals, research articles, and academic documents relevant to the focus of the study. The data obtained is then systematically analyzed to illustrate the relationship between socio-cultural determinants and public health conditions. The results of the study indicate that (1) social determinants such as education level, economic status, access to health services, and environmental conditions have a significant influence on public health behavior; (2) Cultural factors such as traditional beliefs, local values, and social norms contribute to shaping people's health-seeking behavior; and (3) the interaction between social and cultural factors can either strengthen or hinder the success of government-run health programs. However, the implementation of public health policies still faces various challenges, such as low health literacy, strong cultural influences that do not support clean and healthy living behaviors, and unequal access to health services between regions. Therefore, a more adaptive, participatory, and contextual socio-cultural approach is needed in the planning and implementation of public health programs. The novelty of this article lies in the study that not only highlights social determinants as a structural factor, but also emphasizes the role of culture as a value system that dynamically influences public health behavior, as well as the importance of integrating socio-cultural approaches in public health interventions in Indonesia.